Optical N-invariant of graphene’s topological viscous Hall fluid - Todd Van Mechelen (Nature Portfolio, 2021)
Graphene is the archetype for realizing two-dimensional topological phases of matter. Here, the authors introduce a new topological classification connected to polarization transport, where the topological number is revealed in the spatiotemporal dispersion of the susceptibility tensor.